On Accuracy and Stability Analysis of the Reproducing Kernel Space Method for the Forced Duffing Equation - Bahram Asadi; Taher Lotfi (International Journal of Differential Equations)
It is attempted to provide the stability and convergence analysis of the reproducing kernel space method for solving the Duffing equation with with boundary integral conditions. We will prove that the reproducing space method is stable. Moreover, after introducing the method, it is shown that it has convergence order two.